Business networking : innovation and ideas in theory and practice - O'Sullivan, Catherine, 1956 December 5-; O'Sullivan, Terry, 1957- (New York, NY : Routledge, 2022)
"The term 'networking' can mean very different things in different contexts: formal organisational structures, personal or career development, or a technique for increasing sales. This is an approachable book which brings together the basics of all these meanings, underpinned by an overview of multiple theoretical models that support the various approaches to networking. Drawing on mainstream models in the fields of marketing, employability, innovation and organisational studies, Business Networking provides an integrated overview of the process and structure of networking, across a range of contexts. Synthesising theory with practice, features include examples and viewpoints from a range of networking practitioners in each chapter, presented in their own words, as well as chapter summaries and reflective questions. Networking is considered a key skill for students, entrepreneurs and practitioners and, given the explosion of opportunities brought by the digital age for individuals and organizations to operate within a broad and global network, an introduction to maximizing the benefits is timely. This book should be recommended reading for a broad range of postgraduate courses, from relationship marketing and entrepreneurship skills, to employability and degree apprenticeship programmes. It should also be useful for reflective practitioners looking to expand and utilize their networks effectively"--
OCLC-licensed vendor bibliographic record.
Keywords: Business enterprises -- Computer networks; Internet; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Entrepreneurship